An Exploration of Supports Provided for Children Who Are Deaf or Hard of Hearing in both Mainstream and Specialised Preschool Settings in Ireland - Gallagher, Orlaith (Trinity College (Dublin, Ireland). School of Education, 2022)
An Exploration of Supports Provided for Children Who Are Deaf or Hard of Hearing in both Mainstream and Specialised Preschool Settings in Ireland. There is limited research available on the supports for deaf and hard of hearing children in Ireland. Historically, Ireland has provided limited supports to children who are deaf or hard of hearing and their families. Where there was support, it was provided mainly through institutions. Irish support systems can be difficult to navigate, and rarely appear in succinct, concise formats. It is therefore important in contemporary society to acknowledge the educational needs of children who are deaf or hard of hearing in preschool environments. This study investigates the supports provided for children who are deaf or hard of hearing in Ireland, both in specialised and mainstream preschool settings. This is done through a mixed methodological approach using interviews and surveys, to gather information on the supports from educators in mainstream and special settings, as well as specific support professionals, the AIM Early Years Specialists. The research findings indicate that there are various supports available, dependent on educational systems. Government models of support, such as AIM, are highly used and valued within mainstream settings. However, specialised settings often have their own independent and pre- existent models of support for deaf and hard of hearing children. The support available is dependent on varying factors. This often translates back to the parental choice of educational setting. The findings are explored in reference to the literature about delays in language and social emotional development. Concerns are raised regarding the accessibility of support structures in place for children who are deaf or hard of hearing and their families. The differences between support systems available for those in mainstream settings and specialised settings are highlighted, and the varying approaches are examined. The study identifies a need for further research in the area of deaf education in Ireland, particularly those in the preschool years.
Keywords: Early Intervention; Education